2000
DOI: 10.1111/j.1460-9592.2000.00557.x
|View full text |Cite
|
Sign up to set email alerts
|

Epidural sufentanil during paediatric cardiac surgery: effects on metabolic response and postoperative outcome

Abstract: The metabolic and neuroendocrine effects of caudal epidural analgesia were studied during paediatric cardiac surgery. Combined epidural and general anaesthesia (EPI group; n=12) was compared with deep opioid anaesthesia (DOA group; n=12). During anaesthesia and surgery, haemodynamic stability was similar in the two groups. There was no significant difference between groups concerning the metabolic response to surgery but circulating catecholamines were significantly lower in the EPI group during and after surg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 42 publications
1
9
0
Order By: Relevance
“…We believe that the addition of regional nerve blocks to general anesthetics would afford better glycemic control in children. This is in line with the conclusion arrived at in a study showing no significant difference between GA alone versus regional anesthesia and GA in a pediatric population, with regard to the metabolic response [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…We believe that the addition of regional nerve blocks to general anesthetics would afford better glycemic control in children. This is in line with the conclusion arrived at in a study showing no significant difference between GA alone versus regional anesthesia and GA in a pediatric population, with regard to the metabolic response [ 24 ].…”
Section: Discussionsupporting
confidence: 91%
“…At present, sufentanil is the most widely used synthetic opioid with the best analgesic effect in clinical practice. High doses of sufentanil are used in traditional vascular anesthesia, which has the advantage of stable hemodynamics and good analgesic effect and has prominent disadvantages of long duration of respiratory inhibition [ 3 ]. Thus, clarifying the optimal dose of sufentanil can better provide theoretical basis and specific guidance for clinical application [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…Perioperative and postoperative stress responses with caudal narcotics were evaluated previously by the measurement of cortisol, blood glucose, and interleukin (IL)-6. [ 9 11 12 ] The current study assessed the stress response of surgery using CgA as a biomarker for stress. CgA is a 46 kDa protein that is stored as secretory granules in several endocrine and neuronal cells.…”
Section: Discussionmentioning
confidence: 99%
“…As for the hemodynamic disturbances, Bichel et al [ 12 ] demonstrated no difference in hemodynamics between high-dose IV opioids (sufentanil 15 μg/kg) and caudal sufentanil (5 μg/kg). In the present study, the rise in systolic pressure in the caudal morphine group compared to the control group was significantly reduced ( P = 0.006).…”
Section: Discussionmentioning
confidence: 99%